Highly conductive and flexible molybdenum oxide nanopaper for high volumetric supercapacitor electrode. Issue 6 (23rd January 2017) - Huang, Liang; Yao, Bin; Sun, Jiyu; Gao, Xiang; Wu, Jiabin; Wan, Jun; Li, Tianqi; Hu, Zhimi; Zhou, Jun
Abstract : Paper-like electrodes with high conductivity and flexibility hold great potential for assembling high-performance flexible electronic devices. Abstract : Paper-like electrodes with high conductivity and flexibility hold great potential for assembling high-performance flexible electronic devices. In this study, a flexible conductive film was fabricated via vacuum filtration using highly conductive MoO3− x ultralong nanobelts. This film has low sheet resistance of 5.1 Ω sq −1 and exhibits a stable three-dimensional structure even under 1000 times of bending test. Significantly, this free-standing film has a high volumetric capacitance of 652 F cm −3 . Moreover, a symmetric device based on this electrode demonstrates good cycling stability with a capacitance retention of 85.7% after 25 000 cycles. We anticipate that this strategy can also be applied to other three-dimensional flexible porous films based on one-dimensional conductive nanostructure, which could open up new opportunities for energy storage and conversion.